A APP-Sindicato e a formação política das/os educadoras/es na abrangência do Núcleo Sindical de Francisco Beltrão (2007-2014) - Coelho, Denila (2015)
The working class organization throughout history played a key role in winning rights and better work conditions. In order to better understand the struggle story and organization of Paraná education workers, we carried out this research aiming to know and understand the influence and impact caused by the Training School of APP-Union in political and trade union training of the Trade Union in Francisco Beltrão Center - NSFB educators, from 2007 to 2014. The research method was dialectical historical materialism, and the research sources were bibliographies, documents produced by APP-Union, namely, articles in the institutional website, August 30 newspaper, videos, training books, projects and study reports, registration forms and training attendance lists, NSFB minutes, status of the entity, data taken from the Ministry of Education website - SEED, Paraná and Brazil legislation, as well as questionnaires answered by fifty NSFB educators. The union political education was shaped in an important tool for knowledge socialization, consciousness expansion and education workers organization in the State of Paraná. We pointed out the limits and possibilities of the training offered by the School of Education of APP-Union and from the results we present a proposal of training for NSFB. We conclude that despite the difficulties faced by the school, the experience was/is an important work that needs to be intensified to reach the largest possible number of educators. We understand that the training of teachers is strategic because these professionals play an important task which is schooling, that is, they act directly on the education of the whole society. We emphasize that only an education designed by the working class is capable of enabling conditions for the realization of social change long sought by workers.